ENGLISH Analisis Jaringan Sosial tentang Pembingkaian Sherly Tjoanda sebagai Kepemimpinan Perempuan di Aplikasi X dan TikTok - Abiyyu Ahnaf Bayana; Arif Rahman; Ika Arinia Indriyany (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The rapid development of social media has significantly transformed the way political leadership is constructed, distributed, and perceived within the digital public sphere. This transformation becomes more complex in the context of women’s leadership in Indonesia, which continues to face various structural and cultural challenges, including gender bias, stereotypes, and the tendency to evaluate leaders based on personal attributes. This phenomenon is reflected in the emergence of Sherly Tjoanda as a female regional leader who is active on platforms such as X and TikTok, where public conversations about her not only focus on performance and policy issues but also on gender identity, appearance, and emotional closeness to society. The differing characteristics of these platforms further shape the dynamics of interaction and the construction of meaning in digital spaces. This study aims to analyze the construction of women’s leadership by mapping conversation network structures and identifying framing patterns on X and TikTok using a mixed-methods approach that combines Social Network Analysis (SNA) and framing analysis. Data were collected through a scraping process using Python in Google Colaboratory with relevant keywords, then analyzed using Gephi to identify network structures, dominant actors, and interaction patterns, while framing analysis was employed to examine dominant narrative tendencies. The findings indicate that conversation networks on TikTok tend to be more centralized with relatively homogeneous narratives emphasizing leaders’ closeness to the public and engagement with economic welfare issues, while still containing framing that highlights personal attributes and gender identity. In contrast, networks on platform X are more fragmented with a high level of modularity, reflecting the presence of diverse discourse clusters containing support, criticism, and contestation of public opinion. This study concludes that the construction of women’s leadership on social media is shaped not only by policy narratives but also by social processes that both reproduce and challenge gender bias in the digital public sphere.